PENGARUH KETERSEDIAAN MODAL DAN LAHAN TERHADAP PROSES TRANSFORMASI SPASIAL HBE DI KAMPUNG KARANGASEM, SLEMAN - Luluk Rani Puspita; Dwita Hadi Rahmi (ATRIUM: Jurnal Arsitektur, 2018)
Title: The Effect of Capital and Land Availability on The Spatial Transformation Process at Kampung Karangasem, Sleman Kampung Karangasem as one of Kampung located in pheriphery of Yogyakarta has very rapid spatial development since the establishment of UGM and UNY. People’s initiatives to seize this opportunity, make spatial change from housing into home based enterprises. This study aims to determine the effect of capital and land availability on the spatial transformation process of HBE at Kampung Karangasem. Method used in this study is deductive-qualitative. Data collective by “participant as observer” and mapping.The result of this study indicate that the availability of capital and land has an influence of strategy in the process of transformation from house into a home-based enterprises. Limited capital ownership influences the transformation process of horizontal sharing of space, horizontal shifting of space, horizontal extending of space and vertical extending of space. If homeowner have enough capital, it will make transformation vertical extending of space. The influence of the availability of land is the house that still have enough land with sufficient area will choose to use the horizontal extending of space strategy, while the vertical extending of space strategy is chosen if there is no available vacant land.